Influence of boron nitride nanoparticles in the electrical and photoconduction characteristics of planar boron nitride-graphene oxide composite layer - Ahmad, Harith; Thandavan, Tamil Many K. (American Scientific Publishers, 2019)
A modified Iummer’s method is used to obtain a photoconducting material based on boron nitride (BN)– graphene oxide (GO) composite layer. The proposed silver/BN–GO/silver Schottky photodetector was fabricated using a drop-casting technique and electron beam evaporation. It was characterized using field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, Raman spectroscopy, and Fourier-transform infrared spectroscopy. The confine element composition of boron, nitrogen, carbon, and oxygen showed excellent photoconduction toward laser wavelength of a50 nm and output power of 0.7 mW. The dark and illuminated current–voltage characteristics were used to determine the ideality factor and barrier height, which inevitably simplified the transport mechanism in the device. The reported ideality factor of 2.58 suggests the charge transport at the junction and formation of non-amorphous BN–GO composite layer. © 2019 by American Scientific Publishers All rights reserved.